Correction: Decreasing Hepatitis C Virus Infection in Thailand in the Past Decade: Evidence from the 2014 National Survey. - Rujipat Wasitthankasem; Nawarat Posuwan; Preeyaporn Vichaiwattana; Apiradee Theamboonlers; Sirapa Klinfueng; Viboonsak Vuthitanachot; Napha Thanetkongtong; Siriporn Saelao; Monthana Foonoi; Apinya Fakthongyoo; Jamorn Makaroon; Klaita Srisingh; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0149362.].